DIAGNOSTIC UNCERTAINTY IN SPORTS MEDICINE: CHALLENGES IN THE INTERPRETATION OF CORTISOL TESTING - Gabriela Bajor; Wiktoria Jurczyk-Florkiewicz; Zofia Gniadek; Agata Pszczółka; Joanna Kozak; Kacper Melka; Mikołaj Szulewski; Aleksandra Salagierska; Patrycja Machno; Patryk Matuszczak (International Journal of Innovative Technologies in Social Science, 2026)
Background: Cortisol is a key hormone of the hypothalamic-pituitary-adrenal (HPA) axis and plays an essential role in the stress response. In physically active individuals, exercise-induced cortisol elevations are common; however, cortisol testing is often used in the evaluation of Overtraining Syndrome (OTS) despite uncertain diagnostic value and potential for misinterpretation in clinical practice. Material and methods: A structured literature search of PubMed and Google Scholar (1998–2025) was conducted using terms related to cortisol, exercise, overtraining, hypercortisolism and HPA-axis function. Human studies, systematic reviews, meta-analyses and major endocrine guidelines were included. Results: Cortisol responses to exercise are highly variable and influenced by training load, intensity, duration and individual factors. In athletes with suspected OTS, resting and dynamic cortisol measurements show inconsistent results with significant overlap compared to healthy athletes and non-athletic controls. Diagnostic accuracy is further limited by methodological heterogeneity, diurnal variation and biological variability. Numerous non-training factors, including sleep disturbance, psychological stress, illness, medications and endocrine disorders, can elevate cortisol to levels similar to exercise-related responses, increasing diagnostic uncertainty. Conclusions: Cortisol lacks sufficient specificity and sensitivity to serve as an independent diagnostic marker of OTS. Elevated cortisol in athletes should be interpreted within a comprehensive clinical context. Cortisol testing may provide supportive information but should not be used in isolation to diagnose overtraining or guide clinical or training-related decisions.